Outcome of 12 antenatally diagnosed fetal arachnoid cysts: Case series and review of the literature. (March 2015) - De Keersmaecker, B.; Ramaekers, P.; Claus, F.; Witters, I.; Ortibus, E.; Naulaers, G.; Van Calenbergh, F.; De Catte, L.
Abstract Objectives To investigate the natural history, associated abnormalities and outcome of 12 fetuses with arachnoid cyst diagnosed antenatally by ultrasound and magnetic resonance imaging and to compare the outcome with cases in the literature. Methods A retrospective study of all cases of antenatally detected fetal arachnoid cysts was performed in patients referred to a tertiary unit between 2007 and 2013. Associated abnormalities, pregnancy outcome and postnatal follow-up were analyzed. All papers about prenatally diagnosed arachnoid cysts, of the last 30 years, were evaluated (search terms in Pubmed: "prenatal diagnosis", "Arachnoid Cysts"). Results Fetal arachnoid cysts were diagnosed in 12 fetuses, 9 were females. The mean gestational age of diagnosis was 28 1/7 (range 19 1/7–34 2/7 weeks). A total of 9 cases were supratentorial, 3 were located in the posterior fossa. In 10 cases a fetal MRI was performed which confirmed brain compression in 4 out of 5 supratentorial arachnoid cyst. MRI did not reveal other malformations nor signs of nodular heterotopia. Only one fetus presented with additional major anomalies (bilateral ventricumomegaly of >20 mm and rhombencephalosynapsis) leading to a termination of pregnancy. Two neonates underwent endoscopic fenestration of the arachnoid cyst in the first week of life with no additional intervention in childhood. All but one (10/11) had a favorable postnatal outcome. This child suffered from visual impairment at autism was diagnosed at the age of 5. One child had a surgical correction of strabismus later in childhood. In one child the infratentorial arachnoid cyst regressed spontaneously on ultrasound and MRI in the postnatal period. Conclusions The majority of arachnoid cysts in this series are of benign origin and remain stable. Based on the current series and the review of the literature, in the absence of other associated anomalies and when the karyotype is normal, the postnatal overall and neurological outcome is favorable. Large suprasellar arachnoid cysts however, may cause visual impairment and endocrinological disturbances. Rarely associated cerebral or cerebellar malformations are present. Modern postnatal management of suprasellar arachnoid cyst consists of endoscopic cystoventriculostomy.